2007
DOI: 10.1099/vir.0.82744-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel spliced form of the meq transcript in lymphoblastoid cell lines derived from Marek's disease tumours

Abstract: In tumour cell lines established from Marek's disease (MD) lymphomas L-meq is consistently expressed. It contains a 180 bp insertion encoding additional copies of the proline-rich repeat in the meq open reading frame and its product may contribute to the maintenance of MD virus (MDV) latency. In this study, we identified a novel spliced form of the meq transcript in MD-derived lymphoblastoid cell lines and in MDV-infected cells. This transcript, termed Dmeq, encodes an N-terminal 98 aa of the Meq protein and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…Therefore, the amino acid substitutions in the proline direct repeats of Meq in high-virulence MDV strains could correlate with increased transactivation activity of Meq. However, the differences in the Meq transactivation activities observed in this study were moderate compared with that observed between Meq and L-Meq [21]. Therefore, other mutations in Meq or other viral factors may also contribute to MDV virulence.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Therefore, the amino acid substitutions in the proline direct repeats of Meq in high-virulence MDV strains could correlate with increased transactivation activity of Meq. However, the differences in the Meq transactivation activities observed in this study were moderate compared with that observed between Meq and L-Meq [21]. Therefore, other mutations in Meq or other viral factors may also contribute to MDV virulence.…”
Section: Discussioncontrasting
confidence: 80%
“…c Transient expression of Meq constructs in transfected DF-1 cells. Expression patterns of the different Meq constructs were determined by western blotting with antisera against recombinant Meq [21]. Meq expression patterns differed depending on the combination of amino acid residues at positions 283 and 320 as indicated at the bottom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meq is a polymorphic protein and several variants have been characterized, including L-Meq (which contains an insertion of 60 aa between residues190 and 191), S-Meq (which contains a deletion of 41 aa between residues 190 and 191), VS-Meq (which contains a deletion of 92 aa between residues 174 and 175), and ∆Meq (composed of 98 aa from the N-terminal region of Meq and a frame-shifted distinct C-terminus of 30 aa) [27-29] (Figure 4A). Meq and its variants are expressed in MD tumor cells and in MDV-infected cells, but their roles in cytolytic infection and the establishment of latency or transformation have not been elucidated fully.…”
Section: Resultsmentioning
confidence: 99%